A Model of Service Quality Aspects Conveyed in Hotel Advertising - Jebril Ali Alhelalat; Ma'moun A Habiballah (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2017)
Advertisements play a significant role in communicating product information, guarantees and service excellence. This study aims to investigate the role played by hotel advertisements in building customers’ expectation of service quality. After a mixed qualitative and quantitative research on 14 hotel marketing officers and 228 potential customers in Jordan, a model was inherent to study’s results which adopts that advertisements should convey a message of quality through its attractiveness (celebrity endorsement, entertainment, tangibles and appeal), credibility (reliability, promise of quality, slogan, and reasonable price) and information (imagery, risk reduction and message effectiveness). After confirming the model’s validity and its predictability of customers’ perceived quality, recommendations were suggested to hotel managers and marketers; these to help them utilize the model’s constructs in achieving optimal communication for their service quality.